DRUG UTILIZATION PATTERN OF PSYCHOTROPIC DRUGS IN PSYCHIATRIC OUTPATIENT DEPARTMENT IN A TERTIARY CARE TEACHING HOSPITAL - Sabu, Letty; Yacob, Mariya; K, Mamatha; Singh, Hemendra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The growing concern over the burden of psychiatric illnesses in health statistics elicit the importance of rational prescribing of psychotropic drugs. Due to the minimal number of studies conducted in this area, the present study was carried out to assess the morbidity pattern and prescribing trend of drugs used in psychiatric outpatients. Methods: This prospective observational study was conducted for a period of 6-month in a psychiatric outpatient department. The medical records of 202 patients were reviewed for analyzing the prescription pattern using the World Health Organization drug indicators, wherein patients were categorized according to the International Classification of Diseases-10 criteria. Results: In the present study, 129 (63.9%) of the 202 patients were males. The majority of the patients (36.63%) were in the age group of 25-35 years. Substance-related disorders (28.71%) were the most common psychiatric disorders followed by schizophrenia and other psychotic disorders (22.77%). Anxiolytics and hypnotics (31.99%) were the most commonly prescribed psychotropic drug class followed by antipsychotics (20.2%) and antidepressants (18.18%) with clonazepam (47.89%), risperidone (42.5%), and escitalopram (57.4%) being the most common drugs, respectively. Polypharmacy was found in 93.56% of the prescriptions with an average of 3.396 drugs/prescription. Generic drug usage (39.94%) was found to be low when compared to the brand drug usage (60.05%). Conclusion: Benzodiazepines were the most commonly used psychotropic drugs. Polypharmacy, although practiced as a treatment strategy to manage psychiatric illnesses, predisposes patients to adverse events and adherence issues. Â  Keywords: Drug utilization pattern, Psychotropic drugs, Polypharmacy, Psychiatric outpatients.